Children with atopic dermatitis show increased activity of β‐glucocerebrosidase and stratum corneum levels of glucosylcholesterol that are strongly related to the local cytokine milieu. (5th April 2022) - Kezic, Sanja; McAleer, Maeve A.; Jakasa, Ivone; Goorden, Susan M.I.; der Vlugt, Karen Ghauharali‐van; Beers‐Stet, Femke S.; Meijer, Judith; Roelofsen, Jeroen; Nieman, Monique M.; van Kuilenburg, André B.P.; Irvine, Alan D.
Summary: Background: Atopic dermatitis (AD) is characterized by immune dysregulations and an impaired skin barrier, including abnormalities in lipid organization. In the stratum corneum (SC), β‐glucocerebrosidase (GBA) mediates transformation of glucosylceramide (GlcCER) into ceramide (CER) and cholesterol into glucosylcholesterol (GlcChol). Alteration in GBA activity might contribute to skin barrier defects in AD. Objectives: To investigate GBA activity in the SC of children with AD before and after topical corticosteroid therapy and to compare it with healthy controls; to determine SC levels of GlcCER‐ and CER‐containing hydroxysphingosine base (GlcCER[H] and CER[H], respectively) and GlcChol; and to relate them to disease severity, skin barrier function and the local cytokine milieu. Methods: Lipid markers and cytokines of innate, T helper 1 and T helper 2 immunity were determined in SC collected from healthy children and from clinically unaffected skin of children with AD, before and after 6 weeks of therapy with topical corticosteroids. AD severity was assessed by Scoring Atopic Dermatitis and skin barrier function by transepidermal water loss (TEWL). Results: Baseline GBA activity and GlcChol levels were increased in children with AD but declined after therapy. CER[H] levels and the CER[H] to GlcCER[H] ratio were increased in AD. GBA activity and GlcChol correlated with TEWL and levels of multiple cytokines, especially interleukin‐1α and interleukin‐18. GlcChol was strongly associated with disease severity. Conclusions: We show increased GBA activity and levels of GlcChol in AD. Our data suggest an important role of inflammation in disturbed lipid processing. GBA activity or GlcChol might be useful biomarkers in the monitoring of therapeutic responses in AD. What is already known about this topic? Patients with atopic dermatitis (AD) have a reduced skin barrier, mainly caused by altered lipid organization. The mechanisms underlying these lipid anomalies are not fully understood but likely reflect both genetic abnormalities in AD skin and the local cutaneous inflammatory environment. What does this study add? We show increased activity of the ceramide‐generating enzyme β‐glucocerebrosidase in AD. Activity of this enzyme was correlated with the local cytokine milieu and declined after local corticosteroid therapy. We show that glucosylcholesterol levels in the stratum corneum are increased in AD. The function of glucosylcholesterol and the physiological consequences of increased levels are not clear yet; however, its levels were strongly correlated with skin barrier function: high transepidermal water loss strongly correlated with high levels of glucosylcholesterol. What is the translational message? Correction of cutaneous inflammation largely restores alterations in lipid metabolism in the stratum corneum of infants with AD. Abstract :